Optimalisasi Peran Dewan Pengawas Syari’ah (DPS) di Lembaga Keuangan Syari’ah - Neneng Nurhasanah (Fakultas Hukum, Universitas Islam Bandung, 2011)
AbstrakUnder the organization structure of Syariah Financial Institute, the function of Syariah Supervisory Board is to ensure that practice of Syariah Financial Institute is in line with Syariah Principles. However, the role and function of the Syariah Supervisory Council are not optimum in conducting Syariah Financial Institute’s function. There are clear indications that these are happening in the operation of Syariah Financial Institute. Actually, there is regulation on Syariah Supervisory Board, governing role, task, function and authority of Syariah Financial Institute. The purpose of the regulation is to develop the Syariah Financial Institute on the basis of syari’ah much more faster than it is today. This can be achieved due to the supervisory function of the Syariah Supervisory Board and its role as being a catalyst for a syariah economic development. This article is to examine and analyze the optimum use of the Syariah Supervisory Board’s role in the form of socialization on its existence and role to community, especially depositor. This is important to enable member of society to be an element, who can control the Syariah Supervisory Board’s role in Syariah Financial Institutes.